Transformation of Migration Rules from Local to Global - Erkan, Hakan Sezgin (Border Crossing, 2018)
In the 21st century, the scope and the size of migration are more different than previous centuries. The reason behind this is that there are no more global wars or conflicts between states and the economic developments reached the highest levels for some of the countries. Moreover, states try to increase their industrial level. Hence, the conflicts and the economic development level shape migration routes and the destination country. In this context, I will utilize geopolitics and economic development levels to classify countries. As a result of the end of global conflicts and global war, economic conditions became main determinant for migrations in the globalized world in the 21st century. In the 20th century, the scope of migration was small compared to 21st century because of various reasons. Standardized education and high level industrialization are of two main reasons. In the 21st century, the industrialization hit the top level of the world history and education took standardized structure among particular countries. In this research, all countries will be examined in detail with respect to UN Data. Furthermore, the following questions are targeted to be answered: Does migration flow from less developed countries to developed countries? Do developed countries accommodate more immigrants in their borders?